The Academic Triangle Implementation in Bogor New Normal Batik Village as a Collaborative Learning Center - Eneng Tita Tosida; Fredi Andria; Siti Warnasih; Novi Fajar Utami; Elly Sukmanasa; Deden Ardiansyah; Prihastuti Harsani; Dinar Munggaran Achmad; Yuli Wahyuni (Research Collaboration Community (RCC), 2022)
The main objective of this study is build the new normal bogor batik village which is integrated with collaborative learning, so as to create the academic triangle ecosystem. The academic triangle is cyclical in nature, which continues as an ecosystem of education, research and entrepreneurship (not only being an entrepreneur but an entrepreneurial spirit that never gives up in the face of all obstacles). This cycle involves lecturers and students who at the same time have a positive impact on improving the social economy and strengthening local culture. Hopefully, in the end, the ecosystem can become a laboratory for strengthening the academic triangle